2012
DOI: 10.1007/s12230-012-9274-z
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a Real-Time RT-PCR Assay and its Comparison with ELISA, Conventional RT-PCR and the Grow-out Test for Large Scale Diagnosis of Potato virus Y in Dormant Potato Tubers

Abstract: A TaqMan real-time reverse transcription-PCR (real-time RT-PCR) procedure was developed, optimized, and compared with other routine methods to detect Potato virus Y (PVY) in dormant potato tubers. Three pairs of primers and probes were designed and evaluated for their suitability to facilitate the real-time RT-PCR detection of PVY for all strain groups including PVY O , PVY N , PVY N: O (0 PVY N-Wi ) and PVY NTN . Among the primer and probe combinations tested, the combination PVY-1 produced the lowest thresho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 30 publications
(33 reference statements)
0
24
0
4
Order By: Relevance
“…3 . The relative performance of traditional two-step RT-PCR and real-time RT PCR protocols and how they compare to the more common ELISA assay has been studied and reported by Singh et al [ 5 ]. A detailed costing of reagents, equipment, and labor for each protocol is shown in Note 3 .…”
Section: General Laboratory Equipmentmentioning
confidence: 99%
See 2 more Smart Citations
“…3 . The relative performance of traditional two-step RT-PCR and real-time RT PCR protocols and how they compare to the more common ELISA assay has been studied and reported by Singh et al [ 5 ]. A detailed costing of reagents, equipment, and labor for each protocol is shown in Note 3 .…”
Section: General Laboratory Equipmentmentioning
confidence: 99%
“…The mosaic symptoms of PVY are diffi cult to observe on many potato varieties, hampering accurate detection of the virus visually. Also, observation of symptoms can only be done on foliage, and ELISA can only be applied to foliage or tuber sprouts, requiring either fresh tissue during the growing season or signifi cant time and effort in sprouting or grow-out of dormant tubers after harvest [ 5 ]. In addition, there are many strains of PVY that vary in the type and severity of symptoms [ 7 ], and visual observation and ELISA methods are limited in their ability to differentiate them [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detection of potato viruses, based on their protocol, was more sensitive compared to RNA isolated via RNAeasy kit (Singh et al 2002). Moreover it was shown to be beneficial for PVY detection by real time RT-PCR (Singh et al 2012). However, the protocol developed by Singh et al (2002) is composed of many steps, includes sample digestion with DNAse I and proteinase K as well as organic solvents for extraction and precipitation steps (Singh et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Reverse transcription PCR is much more sensitive and since 1990s has been adopted for detection of potato viruses directly in tuber extracts (Spiegel and Martin 1993;Singh and Singh 1996;Singh 1998;Singh et al 2002;Crosslin and Hamlin 2011). Many variations of RT-PCR have been developed focusing on (i) identification and elimination of factors negatively affecting virus detection in tubers (Singh and Singh 1996), (ii) development of standardized protocols (Singh 1998;Crosslin and Hamlin 2011), (iii) simplification of sample preparation (Nolasco et al 1993;Singh et al 2004), (iv) multiplexing (Nie and Singh 2000;Singh and Nie 2003;Du et al 2006;Li et al 2008;) and (v) real time detection (Knorr et al 1996;Boonham et al 2000;Agindotan et al 2007;Mortimer-Jones et al 2009;Singh et al 2012). However, reports comparing performance of RT-PCR (Barker et al 1993;Bolotova et al 2009), and real-time RT-PCR (Fox et al 2005) with grow-out test have shown that the reliability of the latter method is either equal or more.…”
Section: Introductionmentioning
confidence: 99%